(untitled) (Altre Modernità, 2016)
Very few topics mobilize both the "Portuguese thought" -just to use a porous category of difficult definition- and the Portuguese decolonization in the mid-70s, after the Carnation Revolution. Multiple imaginations were elaborated from this event that fractured an expansion and a secular colonial theory. However, as Eduardo Lourenço fully shows (Do colonialismo como nosso impensado, 2014) the dereliction of the Atlantic history produces a multitude of ontological and symbolic specters and critical problems for the country called to articulate a new inscription outside of the Atlantic-Europe dialectics, exclusively turned to the European mythologies and destiny. The article deals especially with the conceptual plan of the Portuguese decolonization, in particular deepening the topic in terms of conceptual history, connected to two involved categories: negation and belonging. A reflection on the temporal tangle of decolonization in particular valorizes the messianic aspect of a "time of the end" leading to a reconsideration of the connection to an event that for some actors of the processes meant a "end of the time".